Utility of a modified components separation for abdominal wall reconstruction in the liver and kidney transplant population - Black, Cara K (Arch Plast Surg, 2019)
BACKGROUND: Incisional hernia is a common complication following visceral organ transplantation. Transplant patients are at increased risk of primary and recurrent hernias due to chronic immune suppression and large incisions. We conducted a retrospective review of patients with a history of liver or kidney transplantation who underwent hernia repair to analyze outcomes and hernia recurrence. METHODS: This is a single center, retrospective review of 19 patients who received kidney and/or liver transplantation prior to presenting with an incisional hernia from 2011 to 2017. All hernias were repaired with open component separation technique (CST) with biologic mesh underlay. RESULTS: The mean age of patients was 61.0±8.3 years old, with a mean body mass index of 28.4±4.8 kg/m(2), 15 males (78.9%), and four females (21.1%). There were seven kidney, 11 liver, and one combined liver and kidney transplant patients. The most common comorbidities were hypertension (16 patients, 84.2%), diabetes (9 patients, 47.4%), and tobacco use (8 patients, 42.1%). Complications occurred in six patients (31.6%) including hematoma (1/19), abscess (1/19), seroma (2/19), and hernia recurrence (3/19) at mean follow-up of 28.7±22.8 months. With the exception of two patients with incomplete follow-up, all patients healed at a median time of 27 days. CONCLUSIONS: This small, retrospective series of complex open CST in transplant patients shows acceptable rates of long-term hernia recurrence and healing. By using a multidisciplinary approach for abdominal wall reconstruction, we believe that modified open CST with biologic mesh is a safe and effective technique in the transplant population with complex abdominal hernias.